ChemInform Abstract: Review: Single‐Molecule Magnets Based on Pyridine Alcohol Ligands. Issue 50 (November 2016) - Bao, Dong‐Xu; Xiang, Shuo; Wang, Jin; Li, Yun‐Chun; Zhao, Xiao‐Qing
Abstract: Review: 72 refs.